THE EFFECT OF BIG BOOKS AS TEACHING MEDIA ON THE THIRD GRADE STUDENTS’ READING COMPREHENSION IN SOUTH BALI - Nalantha, IMD; Artini, LP; Mahayanti, NWS (Universitas Pendidikan Ganesha, 2018)
This study aimed at investigating whether or not there was a significant effect of Big Book as teaching media on the third grade students’ reading comprehension in south Bali. Research design of this study was Quasi Experimental of Post-test Only Control Group Design. The population was 56 students of the third grade students of elementary school in south Bali. Two classes were used as sample of this study. Class IIIA was assigned as experimental group and treated by using Big Book as teaching media. Meanwhile, class IIIB was assigned as control group and treated by using conventional media. The data were analyzed by using t-test through SPSS 16.0. The result of descriptive statistical analysis shows that mean score of experimental group is 80.5357 and control group is 75.3571. It means experimental group gets better score than in control group. The result of inferential statistical analysis shows comparison between tobs (t-observed) and tcv (t-critical value) that is 2.181>2.0049. It means that the value of tobs is higher than the value of tcv. It can be concluded that there is a significant effect on the third grade students’ reading comprehension taught by using Big Book as teaching media.